Internalisasi Nilai-Nilai Akhlak melalui Pembelajaran Sejarah Kebudayaan Islam pada Siswa MI/SD - jurnaldarusalam; Fitri Humaira Azhra; Irma Neni Wahidah; M Hadi Yasin; Baiq Ida Astini (Fakultas Tarbiyah IAI Darussalam, 2026)
This study aims to conduct an in-depth analysis of the process of internalising moral values through the teaching of Islamic Cultural History in primary schools, using a descriptive qualitative approach. The research was conducted in primary schools, involving teachers, pupils and headteachers as subjects selected through purposive sampling based on their relevance to the focus of the study. Data collection was carried out through observation, in-depth interviews, and documentation, with the researcher serving as the primary instrument supported by research guidelines. Data validity was tested through triangulation of sources and methods as well as member checking, whilst data analysis was conducted using an interactive model encompassing data reduction, data presentation, and drawing conclusions. The research findings indicate that the process of internalising moral values has been relatively effective through the integration of values into lesson planning, the application of diverse methods, and teachers’ exemplary conduct in teaching practice. However, this effectiveness has not yet been fully optimised due to constraints on time allocation, the diversity of pupils’ characteristics, and the lack of optimal support from the family environment. Furthermore, a gap was identified between the ideal conditions and the reality of implementation, particularly regarding the development of learning models, the availability of adequate affective assessment tools, and the synergy between schools and families. Therefore, it is necessary to.